System of Good Manufacturing Practices (GMP) for Tofu Products at Sumber Reski Industry, Sendang Mulya District, Konawe City - Mardianta, I Gede; Sarinah, Sarinah; Tamrin, Tamrin (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
The study aims is to identify the application of Good Manufacturing Practices (GMP) and SSOP for tofu products at industry tofu sumber reski, Sendang mulya sub-district, Konawe city and provide recommendations for the best improvements related to the problems of implementing Good Manufacturing Practices (GMP) at Sumber reskit. Every food producer must have quality according to standards so that the food produced is safe for consumption. Data collection comes from direct observations, interviews, evaluations carried out by observing all aspects of Good Manufacturing Practices (GMP) based on the regulation of the Ministry of Industry of the Republic of Indonesia No. 75 of 2010). Identification of the implementation of Good Manufacturing Practices (GMP) at Sumber Reski based on the Minister of Industry Regulation on Good Processed Food Production Methods (CPPOB) with a checklist gap getting a total of 63% of 18 parameters, which means Sumber Reski Industry still has to improve in order to meet the requirements of GMP standards according to Regulations The Minister of Industry of the Republic of Indonesia Number 75/M-IND/PER/7/2010 concerning guidelines for good processed food production.